THE INFLUENCE OF LIQUID ORGANIC FERTILIZER COCONUT WATER AND CHICKEN MANURE ON COCOA (Theobroma cacao L.) PLANT GROWTH - Warsito, Kabul; Alfarizky, Muhammad Dio; Ardiansyah, Agung (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Research on the effect of giving Liquid Organic Fertilizer (LOF) coconut water and chicken manure on the growth of cocoa ( Theobroma cacao L) was carried out from February to July 2022. This study was conducted to determine the effect of giving chicken manure fertilizer and giving coconut water LOF to the growth of cocoa plants and their interactions. This study used a Split Plot Design consisting of 2 treatment factors with 6 combinations and 4 replications so that 24 plots were obtained with a total of 120 research plants. The main plot (main plot) is the provision of chicken manure with the symbol "A" consisting of A0 = No Treatment (Control) and A1 = 200 grams/polybag. The sub plot (child plot) is the provision of coconut water LOF which is given the symbol "K" consisting of K0 = No treatment (control), K1 = 100 ml/polybag and K2 = 200 ml/polybag. Parameters observed were plant height (cm), number of leaves (strands), leaf width (cm), leaf length (cm), dry weight (grams) and also base weight (grams). The results showed the effect of chicken manure on the growth of cocoa plants on plant height (cm), number of leaves, leaf width (cm), leaf length (cm), plant dry weight (grams), and plant wet weight in all parameters observed. showed no significant effect where the best treatment was obtained at A1 (200 grams/polybag). LOF administration of coconut water on the growth of cocoa plants on plant height (cm), number of leaves, leaf width (cm), leaf length (cm), plant dry weight (grams), and plant wet weight in all parameters observed showed no significant effect. There was no interaction between chicken manure fertilizer and coconut water LOF on the observed parameters.